Representações de Ernesto Geisel em obras historiográficas, biográficas e didáticas - Marchiori, Cassiane da Conceição Ramos (2013)
Objective to analyze representations of Ernesto Geisel "given to read" in historical works, biographical and History Textbooks Guide indicated by Textbook in the years 2008, 2011 and 2012. Search also understand the implications of these representations for the appropriation of historical character. The theoretical framework is based on the principles of Cultural History, sticking precisely to the concepts of "representation," ownership "and" practices "presented by Roger Chartier, especially in the work Cultural History: between practices and representations (2002). We note that the authors of history textbooks devoted themselves primarily to describe Ernesto Geisel as president of political détente occurred years after the end of his presidential term. Our hypothesis led us to believe that representations of Ernesto Geisel brought by biographical and inserted into textbooks of history contribute to the enrichment of content and the "human" perspective of history, which proved to be little point in textbooks analyzed. Joints/placements representations Ernesto Geisel in works aimed at different audiences (historiography, biographical and didactic) enable the fluidity of Science History in the daily schooling, and may make it more understandable and concrete (tangible). It is also important to consider whether representations of Ernesto Geisel circulating Textbooks History coincides with depictions exposed in biographical and historiographical order to have, increasingly diverse topics for discussions that provide intellectual development and citizenship in the individual who is inserted feels really, in history. It was identified that there are representations of Ernesto Geisel in biographical and historiographical who communicate with each other, however, this does not occur when entering the textbooks of history in such a comparison, since they do not back clear representations of Ernesto Geisel as an individual incarnated in its historical context, impairing the sensitivity of educating himself about the fact that part of human history. It was also noticed that the textbooks analyzed here are redundant as to the facts by treating the same events and characters, there is no dialogue with other groups who have lived this historical period (1964-1985).